Subjective expectations regarding longevity and future health: a cross‐sectional survey among patients with Crohn's disease. (13th October 2020) - Péntek, M.; Gulácsi, L.; Herszényi, L.; Banai, J.; Palatka, K.; Lakatos, P. L.; Brodszky, V.; Rencz, F.
Abstract: Aim: The aim was to explore the subjective health expectations (sHE) of patients with Crohn's disease (CD) for both the near future and the elderly. Method: A cross‐sectional survey was performed in four gastroenterology centres in Hungary. Consecutive outpatients with CD with age ≥ 18 were recruited. Socio‐demographic and disease characteristics were recorded and the Crohn's Disease Activity Index (CDAI), Perianal Disease Activity Index, Patients' Global Assessment (PGA) and current pain visual analogue scale (VAS) were assessed. Subjective life expectancy (sLE) was explored and compared to statistical life expectancy. Current health and sHE for 1 year ahead and for ages 60/70/80/90 were assessed using the descriptive system of the EQ‐5D‐3L. Results: In all, 206 patients (54.9% men) with a mean age of 34.7 (SD 10.5 years) and disease duration of 10.5 (SD 6.3) years were studied. The CDAI score was 110.5 (SD 77.0) and 66% were treated by biologic drugs. Mean current EQ‐5D‐3L score was 0.80 (SD 0.17) and patients expected a 0.05 (SD 0.15) improvement within a year ( P < 0.05). For ages 60/70/80/90, a mean EQ‐5D‐3L score of 0.59, 0.38, 0.10 and −0.12 respectively was provisioned. Age, current health status, sLE, PGA and pain VAS showed significant correlation with both 1‐year and older age sHE ( P < 0.05). Long‐term sHE and sLE were negatively affected by the presence of extraintestinal manifestations but not by previous CD‐related surgery. Conclusion: Patients with CD expect severe deterioration in health in later life. Given that unrealistic sHE may affect patients' current quality of life and health behaviour, we encourage physicians to explore and consider CD patients' sHE in clinical care.